2013
DOI: 10.2174/1874279301307010090
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Parenteral Antimicrobial Therapy (OPAT) in the Kingdom of Bahrain: Efficacy, Patient Satisfaction and Cost Effectiveness

Abstract: Outpatient parenteral antimicrobial therapy (OPAT) is an alternative method to deliver intravenous antimicrobial agents to patients requiring parenteral therapy without an overnight hospital stay. The aim of this study was to review the OPAT services, to explore patient satisfaction with the services provided, and to determine cost effectiveness. A retrospective review for the raw data collected in the OPAT clinic between February 2012 and January 2013 was included. Patients' variables including age, sex, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
0
24
0
1
Order By: Relevance
“…Only three studies reported on the impact of ASPs on length of stay and/ or mortality metrics [31,32,48]. Bahrain studies on adoption of ASPs in the outpatient department of a military hospital reported that the outpatient service prevented admissions to hospital (2 out of 101 in 2013 and 6 out of 97 in 2015) as a result of their antimicrobial stewardship practices [31,32]. Another study in a Saudi hospital reported reduction of hospital stay to 376 defined daily doses (DDD) compared to 2404 DDD pre-ASP adoption [48].…”
Section: Outcomes Of Hospital Adoption Of Asps In Gcc Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies reported on the impact of ASPs on length of stay and/ or mortality metrics [31,32,48]. Bahrain studies on adoption of ASPs in the outpatient department of a military hospital reported that the outpatient service prevented admissions to hospital (2 out of 101 in 2013 and 6 out of 97 in 2015) as a result of their antimicrobial stewardship practices [31,32]. Another study in a Saudi hospital reported reduction of hospital stay to 376 defined daily doses (DDD) compared to 2404 DDD pre-ASP adoption [48].…”
Section: Outcomes Of Hospital Adoption Of Asps In Gcc Countriesmentioning
confidence: 99%
“…Two studies from Bahrain reported increased use of broad spectrum antibiotics like ceftriaxone due to resistance to first and second line options [31,32]. One Omani study reported that 90% of antibiotic prescriptions were for broad spectrum antibiotics due to lack of adherence with antimicrobial guidelines and policies [40].…”
Section: Outcomes Of Hospital Adoption Of Asps In Gcc Countriesmentioning
confidence: 99%
“…56 Of the remaining studies that considered acceptability in OPAT patients only, most involved multiple OPAT models (and did not differentiate between them in their findings), or did not specify the model(s) under study. In general, satisfaction with treatment was very high, 2,13,27,36,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] including when patients had to have frequent attendance at hospital. 5,84 Commonly perceived advantages of OPAT included the ability to resume daily activities, 2,27,71,73 feelings of improved self-esteem or greater freedom and control, 67,71,73,85,86 and not having to remain in or attend hospital.…”
Section: Patient Acceptabilitymentioning
confidence: 99%
“…5,84 Commonly perceived advantages of OPAT included the ability to resume daily activities, 2,27,71,73 feelings of improved self-esteem or greater freedom and control, 67,71,73,85,86 and not having to remain in or attend hospital. 2,71,82,85,87 The main disadvantages most commonly related to infusion equipment, and included anxiety about the device and its sterility, 35,37,78 the discomfort and limitations imposed by pump devices, 36,37 and issues related to storage. 88 Two studies found that younger patients were better able to use infusion devices, and required less support to do so than older patients.…”
Section: Patient Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation